1986
DOI: 10.2166/nh.1986.0011
|View full text |Cite
|
Sign up to set email alerts
|

Attempting Flow Forecasts of the Indus River, Pakistan Using Remotely Sensed Snow Cover Data

Abstract: Recent developments in collection and interpretation of remotely sensed back radiation data from the earth surface obtained by satellites has made it possible to readily delineate areas covered by snow on the earth surface. In view of this, attempts have been intensified during the last decade to generate statistical relationships between the snow covered area in a basin and the corresponding runoff during the snow-melt period. However, examination of such relationships developed specifically for forecasting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Snow covered area has also been used directly in simple regression equations to derive seasonal runoff in areas such as Pakistan (Rango et al, 1977), India (Ramamoorthi, 1987) and Norway (0strem et al, 1981). Similar work was done by Makhdoom & Solomon (1986) for the Indus River in Pakistan. More recently, Donald et al (1992) used airborne SAR data to detect snow cover extent in a discontinuous ripe snow pack for an area in southern Ontario, Canada.…”
Section: Snow Coyer Mappingsupporting
confidence: 52%
“…Snow covered area has also been used directly in simple regression equations to derive seasonal runoff in areas such as Pakistan (Rango et al, 1977), India (Ramamoorthi, 1987) and Norway (0strem et al, 1981). Similar work was done by Makhdoom & Solomon (1986) for the Indus River in Pakistan. More recently, Donald et al (1992) used airborne SAR data to detect snow cover extent in a discontinuous ripe snow pack for an area in southern Ontario, Canada.…”
Section: Snow Coyer Mappingsupporting
confidence: 52%
“…While these studies have reported better results with time, these conceptual rainfall-runoff models are not useful for longer-term (seasonal) forecasting since they are based on near-real-time daily weather data. In addition, the relationship between snow-covered areas versus streamflow can be complicated by variations of snow depth (Makhdoom and Solomon, 1986). However, snow water equivalent or snow measurement information has not been considered for Satluj Basin flow prediction because such data has not been previously available.…”
Section: Pal Et Al: Predictability Of Western Himalayan River Flowmentioning
confidence: 99%
“…The snowpack parameter most frequently estimated using remote sensing is the amount of snow-covered area as a proportion of a basin under snow cover (Makhdoom and Solomon, 1986). The nature of the snow cover must be characterized adequately if distributed models are to improve hydrological modelling through improved representation of the state variables (Beven, 1989).…”
Section: Satellite Data Processingmentioning
confidence: 99%